The evolution of museum culture in Botswana towards multi-layered architectural heritage conservation - Katlego Pleasure Mwale; Susan Osireditse Keitumetse; Laurence Mwale (ARSNET, 2022)
The role of museums in Botswana has evolved from collecting ethnographic objects and exhibition development to architectural heritage conservation. This paper explores the evolution of museum development through case studies of the National Museum in Gaborone, a regional museum Phuthadikobo Museum in Mochudi, and a privately-owned Botswana Telecommunication Cooperation (BTC) Museum. The study examines exhibition practices in these museums by discussing the limitations of traditional methods of exhibition and argue in favour of a multi-layered exhibition method. Both the National Museum and Phuthadikobo Museum have now transformed into cultural institutions which now undertake architectural heritage conservation projects. These project are include the national museum project which re-creates three huts representative of vernacular architecture of different tribes which we argue is a heritage-making project. The Phuthadikobo community museum proposal for an open-air museum that conserves the existing buildings in-situ and addresses the intersection of heritage conservation, a sense of history, intangible heritage, and lived traditions. Situated within the debates on museum development and heritage conservation, the paper considers how museum development in Botswana could address the challenges of museum exhibition and the questions on heritage authenticity.